Social Transitions Cause Rapid Behavioral and Neuroendocrine Changes - Maruska, Karen P. (Integr Comp Biol, 2015)
In species that form dominance hierarchies, there are often opportunities for low-ranking individuals to challenge high-ranking ones, resulting in a rise or fall in social rank. How does an animal rapidly detect, process, and then respond to these social transitions? This article explores and summarizes how these social transitions can rapidly (within 24 h) impact an individual’s behavior, physiology, and brain, using the African cichlid fish, Astatotilapia burtoni, as a model. Male A. burtoni form hierarchies in which a few brightly-colored dominant males defend territories and spawn with females, while the remaining males are subordinate, more drab-colored, do not hold a territory, and have minimal opportunities for reproduction. These social phenotypes are plastic and reversible, meaning that individual males may switch between dominant and subordinate status multiple times within a lifetime. When the social environment is manipulated to create males that either ascend (subordinate to dominant) or descend (dominant to subordinate) in rank, there are rapid changes in behavior, circulating hormones, and levels of gene expression in the brain that reflect the direction of transition. For example, within minutes, males ascending in status show bright coloration, a distinct eye-bar, increased dominance behaviors, activation of brain nuclei in the social behavior network, and higher levels of sex steroids in the plasma. Ascending males also show rapid changes in levels of neuropeptide and steroid receptors in the brain, as well as in the pituitary and testes. To further examine hormone–behavior relationships in this species during rapid social ascent, the present study also measured levels of testosterone, 11-ketotestosterone, estradiol, progestins, and cortisol in the plasma during the first week of social ascent and tested for correlations with behavior. Plasma levels of all steroids were rapidly increased at 30 min after social ascent, but were not correlated with behavior during the initial rise in rank, suggesting that behavior is dissociated from endocrine status. These changes during social ascent are then compared with our current knowledge about males descending in rank, who rapidly show faded coloration, decreased dominance behaviors, increased subordinate behaviors, and higher circulating levels of cortisol. Collectively, this work highlights how the perception of similar social cues that are opposite in value are rapidly translated into adaptive behavioral and neuroendocrine changes that promote survival and reproductive fitness. Finally, future directions are proposed to better understand the mechanisms that govern these rapid changes in social position.